PEMANFAATAN BAWANG MERAH DAN KULIT BUAH NAGA SEBAGAI UJI DETEKSI BORAKS DAN FORMALIN PADA MAKANAN YANG BEREDAR DI SALAH SATU PASAR TRADISIONAL KOTA BANDUNG - Nursamtari, Raden Ajeng; Rahmadewi, Yulia (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2024)
The lack of awareness of producers in adding dangerous preservatives such as borax and formaldehyde to food for sale on the market is a threat to society. Both ingredients are prohibited for human consumption because they can endanger health. Shallots and dragon fruit skin are believed to be able to detect borax and formaldehyde content in food because both ingredients contain anthocyanin compounds which are part of flavonoids. The aim of this research is to find out how to carry out a borax and formalin detection test by using red onions and dragon fruit skin and to find out whether there is borax and formalin content in food circulating in one of the traditional markets in Bandung. This research is experimental research. The sampling technique used was purposive sampling. The samples used were food circulating in one of the traditional markets in Bandung. Based on the research results, it was found that red onion extract (Allium cepa L.) and dragon fruit (Hylocereus polyrhizus) peel extract positively contained flavonoids. In addition, 3 out of 10 food samples tested positive for formalin and 10 out of 10 food samples did not contain borax. This can be seen through the color change that occurs in the test sample solution. Based on the research results, it can be concluded that red onion extract and dragon fruit peel extract can be effectively used to identify borax and formaldehyde content in food